Methodological procedures for post-occupancy evaluation of a social housing scheme with an emphasis on environmental comfort - Vianna, Nelson Solano (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper refers to the studies developed in the field of environmental comfort, emphasizing the issue of solar access in buildings. The object analysed was a social housing scheme located in the outskirts of the city of São Paulo, built by the local public agency, Companhia de Desenvolvimento Habitacional e Urbano do Estado from the state of São Paulo. The criteria adopted in the assessment of solar access paterns is discussed as well as the performance of individual internal zones of the residential unit, and the final design evaluation from both behavioral and technical points of view.